IMPROVING STUDENTS' SPEAKING ABILITY IN REPORTING PROCEDURAL TEXT BY USING VIDEOS - Kaniadewi, Suci (2017)
The research investigated the use of video to improve students' speaking ability in reporting procedural text to seven-graders of junior high school in Bandung. Quasi-experimental design was used in the research with pre-test post-test non-equivalent group design. The experimental and control groups consisted of 25 students. Data collection was conducted by collecting students' speaking on both pre-test and post-test and conducting questionnaire to experimental class. The data were analyzed using several tests in SPSS 20. The both findings of the test and questionnaire showed that the media was effective in increasing students' speaking scores. This condition was proven by statistical computation of independent t-test on post test scores with tobt is higher than tcrit ( 2.702 > 2.011 ) shows that video as media was considered effective to improve students' speaking ability. The result of the study revealed that video could be effectively to teach speaking procedural text. So that it can be stated that teaching speaking procedural text by using video can improve students' speaking ability. Finally, the findings from the questionnaire showed that most students gave positive responses toward this method. The students gained some benefits from this method such as helping them to improve language skills, creating an active and fun class, motivating them to participate in learning activities.;---Penelitian ini meneliti penggunaan video untuk meningkatkan kemampuan berbicara siswa dalam melaporkan teks prosedural untuk kelas tujuh siswa SMP di Bandung. Desain kuasi-eksperimental digunakan dalam penelitian dengan pre-test post-test non-equivalent group design. Kelompok eksperimen dan kontrol terdiri dari 25 siswa. Pengumpulan data dilakukan dengan cara mengumpulkan kata-kata siswa pada pre-test dan post-test dan melakukan kuesioner di kelas eksperimen. Data dianalisis dengan menggunakan beberapa tes di SPSS 20. Kedua temuan tes dan kuesioner ini menunjukkan bahwa media efektif dalam meningkatkan nilai belajar siswa. Kondisi ini dibuktikan dengan perhitungan statistik uji t independen terhadap nilai post test dengan nilai tobt lebih tinggi dari tcrit (2.702> 2.011) menunjukkan bahwa video sebagai media dianggap efektif untuk meningkatkan kemampuan berbicara siswa. Hasil penelitian menunjukkan bahwa video bisa efektif untuk mengajarkan teks prosedural. Sehingga dapat dikatakan bahwa pengajaran teks prosedural dengan menggunakan video dapat meningkatkan kemampuan berbicara siswa. Akhirnya, hasil dari kuesioner menunjukkan bahwa kebanyakan siswa memberikan tanggapan positif terhadap metode ini. Para siswa mendapatkan beberapa keuntungan dari metode ini seperti membantu mereka meningkatkan kemampuan bahasa, menciptakan kelas yang aktif dan menyenangkan, memotivasi mereka untuk berpartisipasi dalam kegiatan belajar.